On the non-contractual nature of donor-recipient interaction in development assistance - S. Mansoob Murshed (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2008)
This paper analyses three issues in strategic donor-recipient interaction motivated by the complexity of the rationale underlying aid. The first is when we have several principals with conflicting objectives. Any one principal cannot offer high powered incentives to the agent to carry out their designated task. The second is to do with the fact that effort associated with ensuring aid effectiveness may concern both principal and agent; the optimal solution to which requires difficult to design cooperative behaviour. Consequently, the contractual type principal-agent relationship between donors and recipients is inappropriate. We need to consider models that signal recipient quality or commitment to reform. A simple model of signalling with commitment problems is presented, along with extensions to multiple types of agents and time periods, as well as possible solutions involving mechanism design.
Keywords: D72; D82; F35; 330; aid; conditionality; contracting; signalling quality; mechanism design; Entwicklungshilfekonditionen; Anreizvertrag; Prinzipal-Agent-Theorie; Moral Hazard; Theorie